Klebsiella pneumoniae Produces No Histamine: Raoultella planticola and Raoultella ornithinolytica Strains Are Histamine Producers - Kanki, Masashi (American Society for Microbiology, 2002)
Histamine fish poisoning is caused by histamine-producing bacteria (HPB). Klebsiella pneumoniae and Klebsiella oxytoca are the best-known HPB in fish. However, 22 strains of HPB from fish first identified as K. pneumoniae or K. oxytoca by commercialized systems were later correctly identified as Raoultella planticola (formerly Klebsiella planticola) by additional tests. Similarly, five strains of Raoultella ornithinolytica (formerly Klebsiella ornithinolytica) were isolated from fish as new HPB. R. planticola and R. ornithinolytica strains were equal in their histamine-producing capabilities and were determined to possess the hdc genes, encoding histidine decarboxylase. On the other hand, a collection of 61 strains of K. pneumoniae and 18 strains of K. oxytoca produced no histamine.